2012
DOI: 10.1130/ges00750.1
|View full text |Cite
|
Sign up to set email alerts
|

Paleomagnetism of the Crocker Formation, northwest Borneo: Implications for late Cenozoic tectonics

Abstract: Tectonic models for Borneo's Cenozoic evolution differ in several aspects, particularly in the extent to which they include paleomagnetic data suggestive of strong counterclockwise rotation between 30 and 10 Ma. Key areas are undersampled. We present the results of a paleomagnetic study of Eocene to Early Miocene sandstones from northwest Sabah, principally from the Crocker Formation. We obtained reliable site means from 11 locations along a 250 km northeast-southwest transect using thermal demagnetization to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 75 publications
(166 reference statements)
0
20
0
Order By: Relevance
“…Paleomagnetic data reported by Cullen et al () from the Upper Eocene‐Lower Miocene Crocker Formation and the Lower Miocene Kudat Formation reveal CW as well as CCW rotations that may be local rotations related to complex deformation. Field observations (Cullen et al, ) show folded strata with plunging noncylindrical fold axes. In such cases, a more advanced tectonic correction is required (Pueyo et al, ).…”
Section: Paleomagnetic Data Compilationmentioning
confidence: 83%
See 1 more Smart Citation
“…Paleomagnetic data reported by Cullen et al () from the Upper Eocene‐Lower Miocene Crocker Formation and the Lower Miocene Kudat Formation reveal CW as well as CCW rotations that may be local rotations related to complex deformation. Field observations (Cullen et al, ) show folded strata with plunging noncylindrical fold axes. In such cases, a more advanced tectonic correction is required (Pueyo et al, ).…”
Section: Paleomagnetic Data Compilationmentioning
confidence: 83%
“…In such cases, a more advanced tectonic correction is required (Pueyo et al, ). Furthermore, the data from Cullen et al () show a wide spread in inclinations from −84.5° to 48.7°, suggesting syndeformational remagnetization. Fuller et al () also identified that the Crocker Formation experienced remagnetization, as demonstrated by present‐day field overprints.…”
Section: Paleomagnetic Data Compilationmentioning
confidence: 94%
“…13b), and Borneo begins to rotate counterclockwise relative to Sundaland from ∼ 50 to 10 Ma due to oroclinal bending (Hutchison, 2010). Our preferred model invokes collision of the Semitau continental fragment to northern Borneo in the mid-Eocene to induce the ∼ 37 Ma Sarawak Orogeny (Hutchison, 2010) and a potential metamorphic-induced remagnetization event on Borneo at ∼ 35 Ma (Cullen et al, 2012). Northern Palawan accretes to South Palawan, leading to an ophiolite obduction episode and final closure of the proto-South China Sea with the arrival of the Dangerous Grounds and Reed Bank continental blocks by 17 Ma (Hutchison, 1996;Hutchison et al, 2000).…”
Section: The Evolution Of Northern Sundaland and The Opening Of The Smentioning
confidence: 89%
“…Coinciding with the end of sinistral motion along the Red River fault at ∼ 17 Ma (Leloup et al, 1995), spreading in the South China Sea ceased (Briais et al, 1993), likely due to the docking of the Dangerous Grounds-Reed Bank continental fragment onto northern Sundaland (Hutchison, 2004;Hutchison et al, 2000). Recent work by Cullen et al (2012) indicates a strong counterclockwise rotation of Borneo between 30 and 10 Ma, and they acknowledge that an earlier counterclockwise rotation was likely overprinted by a ∼ 35 Ma remagnetization event. The relative motion between Borneo and stable Eurasia is accommodated by the subduction of the proto-South China Sea, meaning that the CW rotation of Indochina resulting from extrusion tectonics is compatible with the large CCW rotation of Borneo resulting from oroclinal bending.…”
Section: The Evolution Of Northern Sundaland and The Opening Of The Smentioning
confidence: 98%
See 1 more Smart Citation